Navigating the manufacturing process and ensuring the quality of regenerative medicine therapies : proceedings of a workshop - Markowitz-Shulman, Ariel (Online access: NCBI NCBI Bookshelf., 2017)
On June 26, 2017, the Forum on Regenerative Medicine hosted a public workshop in Washington, DC, titled Navigating the Manufacturing Process and Ensuring the Quality of Regenerative Medicine Therapies in order to examine and discuss the challenges, opportunities, and best practices associated with defining and measuring the quality of cell and tissue products and raw materials in the research and manufacturing of regenerative medicine therapies. The goal of the workshop was to learn from existing examples of the manufacturing of early-generation regenerative medicine products and to address how progress could be made in identifying and measuring critical quality attributes. The workshop also addressed the challenges of designing and adhering to standards as a way of helping those who are working to scale up processes and techniques from a research laboratory to the manufacturing environment. This publication summarizes the presentations and discussions from the workshop.